2014
DOI: 10.1007/s00442-014-3006-7
|View full text |Cite
|
Sign up to set email alerts
|

Woody plant phylogenetic diversity mediates bottom–up control of arthropod biomass in species-rich forests

Abstract: Global change is predicted to cause non-random species loss in plant communities, with consequences for ecosystem functioning. However, beyond the simple effects of plant species richness, little is known about how plant diversity and its loss influence higher trophic levels, which are crucial to the functioning of many species-rich ecosystems. We analyzed to what extent woody plant phylogenetic diversity and species richness contribute to explaining the biomass and abundance of herbivorous and predatory arthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 70 publications
3
46
0
Order By: Relevance
“…Our results conform with previous findings on diversity relationships among individual taxa in our study system as well as in others 9, 16, 34 . These findings emphasize the important role of plant communities in directly structuring community patterns not only of herbivores, but also of predators and parasitoids 35 , in the aboveground forest compartment.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Our results conform with previous findings on diversity relationships among individual taxa in our study system as well as in others 9, 16, 34 . These findings emphasize the important role of plant communities in directly structuring community patterns not only of herbivores, but also of predators and parasitoids 35 , in the aboveground forest compartment.…”
Section: Discussionsupporting
confidence: 94%
“…The comparatively weak connections across trophic levels in the richness and diversity analyses (especially between plants and herbivores) deviate from the findings of a similarly comprehensive study 12 , which, however, was conducted in a much less complex, experimental grassland system and did not differentiate among groups of herbivores or predators. On the other hand, our results are consistent with those of previous studies on individual trophic groups in our study system, which found that many effects of woody plant species richness or diversity acted on higher trophic level abundance rather than on richness or diversity patterns 34, 53, 54 . Moreover, species richness relationships among plants, arthropods, and microorganisms in our studied forests were found to be highly non-linear across spatial scales 39 .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Many grasshoppers have a relatively broad host plant spectrum (Bernays & Chapman ), and the same probably applies to dominant caterpillars in our study region (see Schuldt et al . ,b). Increases in the abundance (e.g.…”
Section: Discussionmentioning
confidence: 99%